Metrology of pH Measurements in Brackish Waters—Part 2: Experimental Characterization of Purified meta-Cresol Purple for Spectrophotometric pHT Measurements - Müller, Jens D.; Rehder, Gregor (Frontiers in Marine Science, 2018)
Spectrophotometric pH measurements allow for an accurate quantification of acid-base equilibria in natural waters, provided that the physico-chemical properties of the indicator dye are well known. Here we present the first characterization of purified m-Cresol Purple (mCP) directly linked to a primary pH standard in the salinity range 5–20. Results were obtained from mCP absorption measurements in TRIS buffer solutions. The pHT of identical buffer solutions was previously determined by Harned cell measurements in a coordinated series of experiments. The contribution of the TRIS/HCl component to the ionic strength of the buffer solutions increases toward lower salinity: This was taken into account by extrapolating the determined pK2e2 to zero buffer concentration, thereby establishing access to a true hydrogen ion concentration scale for the first time. The results of this study were extended with previous determinations of pK2e2 at higher and lower salinity and a pK2e2 model was fitted to the combined data set. For future investigations that include measurements in the salinity range 5–20, pHT should be calculated according to this pK2e2 model, which can also be used without shortcomings for salinities 0–40 and temperatures from 278.15 to 308.15 K. It should be noted that conceptual limitations and methodical uncertainties are not yet adequately addressed for pHT determinations at very low ionic strength.